Breast liposarcoma with solitary metastasis to the pleura: A case report. Issue 27 (July 2017) - Lei, Lei; Chen, Zhanhong; Wang, Zhuo; Zheng, Linfeng; Zheng, Yabing; Wang, Xiaojia; Wang, Xian
Abstract: Rationale: Breast cancer is the most prevalent malignancy in women worldwide. Our patient presented with a history of breast liposarcoma (LPS) and was found to have pleural metastasis during the initial workup. Patient concerns: The patient was complaining about chest pain and dyspnea that had persisted for a week. Diagnoses: After a full evaluation and histological diagnosis, she was diagnosed as metastatic breast LPS. Interventions: We adopted 6 cycles of pegylated liposomal doxorubicin (PLD) plus ifosfamide as 1st-line palliative chemotherapy, combined with local pleural effusion management. Outcomes: The patient's symptoms were notably relieved, and both malignant metastatic lesions and pleural effusion were controlled. Lessons: Although metastatic breast LPS is rarely reported and incurable, more clinical experience and use of next-generation sequencing should be helpful in finding the effective treatment for metastatic LPS.